An analysis of the Philippine Index Medicus Abstracts 1996-2000 to determine the growth trends of medical specializations in the Philippines - Villamil, Alejandro Daniel G.; Rosal, Rosvida R. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
The Philippines has been facing a growing brain drain of medical health professionals for a number of years. Less and less students are choosing to become doctors and more and more are going into nursing. Faced with this situation, the government opted to promote medical tourism. Their program sought to attract foreign patients looking for cheap but good quality health care. The Philippines needs to offer more than just affordable health care. Quality of care must always be improving and, to attract patients, the country needs to be at the forefront of medical research and innovation. The questions then arise: How do you quantify the growth of the field of medical science in the Philippines? How has the brain drain affected the health industry, particularly among the different specialties in medicine? Which specialties are growing and which are in decline? Policy makers in the government and health industry need answers to these questions. They need to find out which areas of medicine in the Philippines they can promote and which ones they have to encourage to grow. A good indicator of growth of a particular field is the number of research papers being published. The trend in growth of medical specializations can be determined by counting the number of articles they publish over a period of time.
This study did a bibliometric analysis of the Philippine Index Medicus Abstracts (PIMA), 1996-2000 to determine the growth trends of medical specializations in the Philippines for that period .Each entry of the PIMA, 1996-2000 was classified by year under one of thirty five medical specializations. For each specialty, the growth trend was determined using descriptive statistical techniques. It was found that, in general, medical research in the Philippines went through a period of decline from 1996 to 2000. More specifically, out of 35, 19 (54.3) specialties were in decline, 11 (31.4) has a constant rate, and only 5 (14.3) had experienced growth. Factors that could have affected the decline of medical research in the Philippines could have been the recent brain drain. And, it might also have been because of the Asian financial crisis of 1997.The government and other medical institutions have to do more to promote medicine and medical research in the country. The information gathered in this study could be used to point the direction in which policy makers should move to solve the challenges they face in the medical industry.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Philippines Index Medicus; Medicine -- Specialties and specialists -- Philippines